Efficacy of Portable Accelerometer-Based Navigation Devices versus Conventional Guides in Total Knee Arthroplasty: A Meta-analysis - Sun, Han; Li, Shuxiang; Wang, Kun; Wu, Guofeng; Zhou, Jian; Sun, Xiaoliang (The Journal of Knee Surgery, 2020)
Various studies have provided different conclusions regarding which component's alignment can be actually improved by a novel portable accelerometer-based navigation device (PAD) compared with the conventional guide (CON); the operative times and clinical outcomes reported by these studies also exhibited incongruity. Thus, this meta-analysis was conducted to evaluate the efficacy of PADs in total knee arthroplasty (TKA). The Web of Science, EMBASE, PubMed, MEDLINE, and Cochrane Library databases were systematically searched. Studies published till July 2018 and comparing PAD with CON in treatment with TKA were identified. Sixteen studies in which 1,551 TKAs were reported were included. Results showed that PAD was significantly superior to CON in reducing tibial component alignment out of ±3 degrees, femoral coronal angle out of ±3 degrees, and overall mechanical alignment out of ±3 degrees. PAD can also help obtain a more accurate result of femoral coronal angle (degree); however, it requires a longer operative time than the CON group. The two groups were comparable in tibial component alignment out of ±2 degrees, tibial component posterior slope out of ±3 degrees, tibial component posterior slope out of ±2 degrees, femoral coronal angle out of ±2 degrees, femoral sagittal angle out of ±3 degrees, femoral sagittal angle out of ±2 degrees, tibial component alignment (degree), tibial component posterior slope (degree), femoral sagittal angle (degree), overall mechanical alignment (degree), blood loss, Knee Society knee score, Knee Society function score, Oxford Knee Score, Short Form-36 physical component score, Short Form-36 mental component score, and range of motion. In conclusion, compared with CON, PAD can help improve the femoral coronal angle as well as decrease the outliers out of ±3 degrees in femoral/tibial coronal angles and overall mechanical alignment. However, PAD did not show significant advantages in tibial and femoral component sagittal angles out of ±3 degrees, various outliers of ±2 degrees, most mean values of component alignments, operative time, and various functional or satisfactory scores.
Keywords: knee arthroplasty; conventional guides; computer-assisted navigation systems; accelerometers; hand-held navigation; meta-analysis